Devil in the white city : murder, magic, and madness at the fair that changed America - Larson, Erik (London; Bantam Books, 2003)
The novel is a historical account of the exposition in Chicago at the beginning of last centuries.
Keywords: Illinois--Chicago; Mudgett, Herman W; Burnham, Daniel Hudson